2007
DOI: 10.1002/pbc.21012
|View full text |Cite
|
Sign up to set email alerts
|

Complementary/alternative medicine use in a pediatric oncology unit in Turkey

Abstract: More than half of the patients used CAM, with stinging nettle being the most common agent. Our patients place a high level of trust in their physicians and the conventional therapies offered by them; however, they also believe that the complementary therapies are harmless and, therefore, worth trying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
6
20

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(96 citation statements)
references
References 26 publications
(36 reference statements)
6
64
6
20
Order By: Relevance
“…In the USA, prayer, exercise, and spiritual healing were the most often CAM used [16]. In Pakistan, herbal medicine is a widely used form of CAM [17], and in Turkey, herbal medicine and biologics such as honey of Anzer were mostly used [18]. The types of CAM used may be in part explained by cultural habits, religious beliefs as well as availability, at low or no cost, and natural supplement is safe.…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, prayer, exercise, and spiritual healing were the most often CAM used [16]. In Pakistan, herbal medicine is a widely used form of CAM [17], and in Turkey, herbal medicine and biologics such as honey of Anzer were mostly used [18]. The types of CAM used may be in part explained by cultural habits, religious beliefs as well as availability, at low or no cost, and natural supplement is safe.…”
Section: Discussionmentioning
confidence: 99%
“…A study on 1230 pediatric subjects conducted in south-west England also revealed herbal tea as the mostpreferred CAM modality (24%) [17]. Di erent studies on pediatric cancer patients in Turkey showed that herbal products were used by 71.4 -90.7% of patients [14,15]. A South Australian study reported that 33.5% of children received herbal products [6].…”
Section: Discussionmentioning
confidence: 99%
“…e questionnaire was prepared with the cooperation of two centers (Kirikkale University and Gaziantep University), based on a review of published subject-related data . A pilot study was carried out to test the comprehensibility of the questions [2,[13][14][15][16]. ese data were then used to develop the nal version of the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…O TC baseado nas terapias naturais foi o predominante dentre os estudos, tais como: chás, plantas, fitoterapias, homeopatias, multivitaminas (AL-QUDIMAT, 2010;ARUSH, 2006;ELIAS, 2006;GENC, 2009;GENTIL 2010;GÓMES-MARTÍNEZ, 2007;KARADENIZ, 2007;KARALI, 2011;LAENGLER et al, 2008;LANGLER et al;MOLASSIOTS, 2004;NDAO et al, 2013;SÁNCHEZ, 2011;TOMLINSON, 2011;WATT, 2012;WEYL BEN LIM, 2006). Em 2011, um estudo realizado no Líbano, levantou a utilização de terapias culturais não-convencionais e revelou que 19% dos pais das crianças e adolescentes com câncer utilizavam como tratamento complementar as cinzas de ossos humanos (NAJA, 2011).…”
Section: A) Tipos De Tratamentos Alternativos E Complementares Utilizunclassified
“…A maioria dos pais entrevistados manifestou necessidade de obter informação vinda da equipe médica, além de um canal aberto para uma comunicação sobre esse tipo de terapêutica. Os profissionais de saúde devem permanecer informados sobre os benefícios e os efeitos adversos das TAC para discutir as opções de tratamento com os pacientes e suas famílias e para monitorar a sua eficácia (ELIAS, 2006;FLETCHER, 2004;GENTIL, 2010;;GOZUM, 2007;HAMIDAH, 2009;MCCURDY, 2003;MOLASSIOTIS, 2004;NDAO, 2013;O'CONNOR, 2013; Metade dos estudos incluídos nesta revisão mostraram que a maior parte dos pais ou cuidadores não revelou ou discutiu sobre o uso do TAC com os profissionais de saúde envolvidos no tratamento oncológico da criança ou adolescente (AL- QUDIMAT, 2010;ELIAS, 2006;GENC, 2009;GENTIL, 2012;GÓMEZ-MARTÍNEZ, 2007;GOZUM, 2007;KARADENIZ, 2007;O'CONNOR, 2013;LIM, 2006;NAJA, 2011;WEYL, 2006). Somente em um dos estudos incluídos na revisão, os participantes ficaram divididos entre revelar e não revelar sobre uso do TAC, ou seja, 50% referiram discutir com os profissionais sobre o assunto enquanto que a outra metade não o fizeram (NDAO, 2013).…”
Section: B) Motivações Para a Busca Dos Tratamentos Alternativos E Counclassified